Impact of the 9 March 2023 Amendments to the Labour Code on Employment Stability Guarantees for Employees Exercising Rights Related to Parenthood and Caring for Another Family Member - Serafin, Katarzyna (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
The amendment to the Labour Code of 9 March 2023 implemented two EU directives into the Polish legal order - Directive 2019/1152 on transparent and predictable working conditions in the EU and Directive 2019/1158 on work-life balance for parents and carers. The implementation results in new entitlements related to parenthood and caring for another family member, as well as changes to the general and specific protection against termination of employment and guarantees of return to work in employee's current position. In the study, the author analyses how the amendments to the Labour Code have affected the protection of employment stability for employees exercising rights related to parenthood and caring for another family member.